Restricted conformational flexibility of a triphenylamine derivative on the formation of host-guest complexes with various macrocyclic hosts - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Das, Amitava (Chemistry a European Journal, 2012)
Herein, we report the host–guest-type complex formation between the host molecules cucurbit[7]uril (CB[7]), β-cyclodextrin (β-CD), and dibenzo[24]crown-8 ether (DB24C8) and a newly synthesized triphenylamine (TPA) derivative 1X3 as the guest component. The host–guest complex formation was studied in detail by using 1H NMR, 2D NOESY, UV/Vis fluorescence, and time-resolved emission spectroscopy. The chloride salt of the TPA derivative was used for recognition studies with CB[7] and β-CD in an aqueous medium. The restricted internal rotation of the guest molecule on complex formation with either of these two host molecules was reflected in the enhancement of the emission quantum yield and the average excited-state lifetime for the triphenylamine-based excited states. Studies with DB24C8 as the host molecule were performed in dichloromethane, a medium that maximizes the noncovalent interaction between the host and guest fragments. The Förster resonance energy transfer (FRET) process involving DB24C8 and 1(PF6)3, as the donor and acceptor fragments, respectively, was established by electrochemical, steady-state emission, and time-correlated single-photon counting studies.